2011
DOI: 10.1038/bjc.2011.292
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of advanced hepatocellular carcinoma with very low levels of amplitude-modulated electromagnetic fields

Abstract: Background:Therapeutic options for patients with advanced hepatocellular carcinoma (HCC) are limited. There is emerging evidence that the growth of cancer cells may be altered by very low levels of electromagnetic fields modulated at specific frequencies.Methods:A single-group, open-label, phase I/II study was performed to assess the safety and effectiveness of the intrabuccal administration of very low levels of electromagnetic fields amplitude modulated at HCC-specific frequencies in 41 patients with advance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
111
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(118 citation statements)
references
References 32 publications
7
111
0
Order By: Relevance
“…One group, TheraBionic, has previously shown intrabuccal administration of low levels of amplitude-modulated electromagnetic fields (EMF) to either shrink tumor size or maintain stable disease in patients with advanced hepatocellular carcinoma (72). Tolerability studies have also been demonstrated in advanced breast cancer (73).…”
Section: Future Directions and Other Technologiesmentioning
confidence: 99%
“…One group, TheraBionic, has previously shown intrabuccal administration of low levels of amplitude-modulated electromagnetic fields (EMF) to either shrink tumor size or maintain stable disease in patients with advanced hepatocellular carcinoma (72). Tolerability studies have also been demonstrated in advanced breast cancer (73).…”
Section: Future Directions and Other Technologiesmentioning
confidence: 99%
“…Epidemiological studies have shown that exposure to extremely low frequency electromagnetic fields ((ELFEMFs) may be associated with Alzheimer's disease (García et al, 2008), amyotrophic lateral sclerosis (Zhou et al, 2012), childhood asthma (Li et al, 2011) and cancer (Chen et al, 2013), especially childhood leukemia (Schüz, 2011;Grellier et al, 2014) and many other kinds of diseases. However, laboratory studies have not been able to reproduce the results obtained in the epidemiological investigations, but they did show that ELF-EMF (Pesce et al, 2013) plays a beneficial role in wound healing in cancers (Costa et al, 2011) and diseases associated with the nervous system (Di Lazzaro et al, 2013). These data suggest that ELF-EMFs can produce beneficial or harmful pleiotropic effects in organisms or cells.…”
Section: Introductionmentioning
confidence: 66%
“…Reported clinical benefits from using the specific EMF signals to treat advanced hepatocellular carcinoma, stabilizes the disease and even produces partial responses in a subset of the patients (Pesce et al 2013). The basic mechanisms by which this weak EL-EMF interacts with living matter are currently unknown, although several mechanisms have been proposed to account for the initial interactions with cells (Costa et al 2001). The basic mechanism is the forced-vibration of all free ions on the surface of a cell membrane that is caused by an external oscillating field and it has been shown that this coherent vibration of electric charge is able to irregular gate electrosensitive channels on the plasma membrane and cause disruption of the cells' normal electrochemical balance (Costa et al 2001).…”
Section: Introductionmentioning
confidence: 99%